Phylogenetic characterization of Babesia canis vogeli in dogs in the state of Goiás, Brazil Caracterização filogenética de Babesia canis vogeli em cães do estado de Goiás, Brasil - Sabrina Castilho Duarte; Juliana Alves Parente; Maristela Pereira; Célia Maria de Almeida Soares; Guido Fontgalland Coelho Linhares (Revista Brasileira de Parasitologia Veterinária, 2011)
The genus Babesia comprises protozoa that cause diseases known as babesiosis. Dogs are commonly affected by Babesia canis or Babesia gibsoni. Babesia canis is divided into the subspecies Babesia canis canis, Babesia canis vogeli and Babesia canis rossi. Among these, Babesia canis vogeli predominates in Brazil. The objective of this study was to conduct a phylogenetic analysis on Babesia isolates from dogs in Goiânia, Goiás. Blood samples were obtained from 890 dogs presenting clinical signs suggestive of canine babesiosis that were attended at a veterinary hospital of Goiás. Only samples presenting typical intraerythrocytic parasites were used in the study. These were subjected to DNA extraction and amplification of a fragment of the 18S rRNA, by means of PCR. The PCR products were purified and sequenced. Sequences were obtained from 35 samples but only 17 of these were kept after quality assessment. Similarity analysis using BLASTn demonstrated that all 17 sequences corresponded to B. canis vogeli. Analysis using the Mega4 software showed that the isolates of B. canis vogeli from dogs in Goiânia present a high degree of molecular similarity (99.2 to 100%) in comparison with other reference isolates from other regions of Brazil and worldwide, deposited in GenBank. O gênero Babesia compreende protozoários causadores de enfermidades denominadas babesioses. Cães geralmente são acometidos por Babesia canis ou Babesia gibsoni, sendo a primeira classificada em subespécies Babesia canis canis, Babesia canis vogeli e Babesia canis rossi. Entre essas, Babesia canis vogeli predomina no Brasil. O objetivo desse trabalho foi realizar estudo filogenético de amostras de Babesia em cães, em Goiânia, Goiás. Amostras de sangue foram obtidas de 890 cães atendidos no Hospital Veterinário de Goiás, apresentando sinais clínicos de babesiose. Somente amostras com presença de parasitos intraeritrocitários típicos foram utilizadas. Estas foram submetidas a extração de DNA e amplificação de fragmento do gene 18S rRNA pela PCR. Os produtos de PCR foram purificados e sequenciados. Foram sequenciadas 35 amostras, das quais apenas 17 foram mantidas após avaliação de qualidade. A análise de similaridade fornecida pelo BLASTn demonstrou que as 17 sequências deste estudo eram correspondentes a Babesia canis vogeli. Pela utilização do programa Mega4, foi possível verificar que as amostras de Babesia canis vogeli, provenientes de cães da cidade de Goiânia, apresentam, alto grau de similaridade molecular (99,2 a 100%) com isolados de referência de outras regiões do Brasil e do mundo, depositados em GenBank.